Biological growth as an alternative approach to on and off-Earth construction - Brandić Lipińska, Monika; Maurer, Chris; Cadogan, Dave; Head, James; Dade-Robertson, Martyn; Paulino-Lima, Ivan Glaucio; Liu, Chen; Morrow, Ruth; Senesky, Debbie G.; Theodoridou, Magdalini; Rheinstädter, Maikel C.; Zhang, Meng; et al. (Frontiers in Built Environment, 2022)
A critical aspect of human space exploration and eventual settlement is the ability to construct habitats while minimizing payload mass launched from Earth. To respond to this challenge, we have proposed the use of fungal bio-composites for growing extra-terrestrial structures, directly at the destination, significantly lowering the mass of structural materials transported from Earth and minimizing the need for high mass robotic operations and infrastructure preparations. Throughout human history, the construction of habits has used biologically produced materials, from bone and skins to wood and limestone. Traditionally, the materials are used only after post-mortem. Currently, the idea of working with living biological organisms, and the phenomenon of growth itself, is of increasing interest in architecture and space applications. Here, we describe the use of mycelium-based composites as an alternative, biological approach for constructing regenerative and adaptive buildings in extreme environments and extraterrestrial habitats. It is a continuation of our research program initiated under the auspices of the ‘Myco-architecture Off Planet’ NASA NIAC Team. These composites, which are fire-resistant, and insulating, do not consist of volatile organic compounds from petrochemical products and can be used independently or in conjunction with regolith, could employ the living biological growth in a controlled environment, for the process of material fabrication, assembly, maintenance, and repair, providing structures resilient to extra-terrestrial hazards. Here we outline the potential and challenges of using bio-composites for Earth and space applications. We describe how these might be addressed in order to make this biological approach feasible, providing new, growing materials for designing and building sustainable habitats, both on Earth and for long-duration space missions.